PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI MASALAH PESERTA DIDIK PINDAHAN DI SMP PERTIWI 2 PADANG - Palni, Masri Deby (Bimbingan dan Konseling, 2014)
This research is motivated by the existence of a troubled transfer student at a new school, but the role of guidance and counseling teachers in addressing students moving not maximized. The purpose of this study was to determine the role of guidance and counseling teachers in addressing students moving views of the function of understanding, prevention, and eradication. This research was conducted through qualitative descriptive approach. As for the informants of this study were: teacher guidance and counseling, transfer students, friends, and homeroom. The instrument used was the interview, while the techniques used in data processing is data reduction, data display, and conclusion. The results obtained are: (1) Guidance and Counseling teachers role in addressing the problem of students moving views of understanding the function of which is (a) provide an understanding of the school rules, (b) Provide information about effective learning (2) In terms of prevention function is (a) in collaboration with other school personnel to create a school environment and comfortable learning environment for students moving (b) in collaboration with subject teachers to improve student learning motivation (3) In terms of the function of reduction is (a) alleviating the problem transfer students with individual counseling (b) in collaboration with parents of students moving in order to control the activity of their children at home .